Crystal structure of tetraaqua(dimethylformamide)tetrakis(μ-N,2-dioxidobenzene-1-carboximidato)tetrakis(μ-trimethylacetato)tetramanganese(III)sodiumyttrium–dimethylformamide–water (1/8.04/0.62) - Travis, Jordan R. (Acta Crystallogr E Crystallogr Commun, 2015)
The synthesis and crystal structure for the title compound, [YNaMn(4)(C(7)H(4)NO(3))(4)(C(5)H(9)O(2))(4)(H(2)O)(3.76)(C(3)H(7)NO)(0.24)]·8.04C(3)H(7)NO·0.62H(2)O or [Y(III)Na(OTMA)(4)[12-MC(Mn(III)N(shi))-4](H(2)O)(3.76)(DMF)(0.24)·8.04DMF·0.62H(2)O, where OTMA is trimethylacetate, MC is metallacrown, shi(3−) is salicylhydroximate, and DMF is N,N-dimethylformamide, is reported. The macrocyclic metallacrown consists of an –[Mn(III)–N–O](4)– ring repeat unit, and the metallacrown captures one Y(III) ion and one Na(I) ion in the central cavity on opposite faces of the metallacrown. Overall the metallacrown is domed towards the side of the Na(I) ion. Both the Y(III) and Na(I) ions are eight-coordinate, and the trimethylacetate anions bridge the central Y(III) to each ring Mn(III) ion. The ring Mn(III) ions are six-coordinate with a tetragonally distorted octahedral geometry.